Identification of the Changbaishan ‘Millennium’ (B-Tm) eruption deposit in the Lake Suigetsu (SG06) sedimentary archive, Japan: Synchronisation of hemispheric-wide palaeoclimate archives - McLean, D; Albert, P; Nakagawa, T; Staff, R; Suzuki, T; Smith, V; Members, S (Elsevier, 2016)
The B-Tm tephra, dispersed during the highly explosive Changbaishan ‘Millennium’ eruption (ca. 940–950 CE) and a key marker layer within the Greenland ice cores, has now been identified in the Lake Suigetsu (SG06) sedimentary sequence, central Japan. The major element geochemistry of the volcanic glasses within this tephra layer are compared to a new glass dataset from the distal type-locality (Tomakomai Port, Hokkaido) and other published ‘Millennium’ eruption/B-Tm deposits, to verify this correlation. The discovery of the B-Tm tephra in the Lake Suigetsu record provides, to date, the most southerly identification of this ash and, crucially, the first direct tie-point between this high-resolution, mid-latitude palaeoclimate archive and the Greenland ice cores. These findings present significant encouragement for on-going research into the tephrostratigraphy of East Asia, focusing on the identification of widely-dispersed tephra layers which can facilitate the synchronisation of disparate palaeoclimate archives and thus enable the assessment of spatio-temporal variations in past climatic change.